Oil Content, Saturated and Unsaturated Fatty Acids of Some Linseed (Linum usitatissimum L.) Genotypes - Endes, Zuleyha; Er, Fatih; Musa Özcan, Mehmet; Al Juhaimi, Fahad (Asian Journal of Chemistry, 2013)
The main fatty acid components of genotypes identified by gas chromatography were linolenic acid (48.3 %), linoleic acid (11.5 %), oleic acid (30 %), palmitic acid (5.8 %), stearic acid (6.7 %), palmitoleic acid (0.41 %). According to the results, oil rates of genotypes were in the range of 24.5-28.8 and 12.5 % of these ratio was saturated, 90 % was unsaturated fatty acids. It was determined that microbial fertilizer had importance on stearic (p < 0.01) and linolenic (p < 0.05) fatty acids statistically.